Changes of serum paraoxonase (an HDL-cholesterol-associated lipophilic antioxidant) and arylesterase activities in severe preeclamptic women - Kumru, S; Aydin, S; Gursu, MF; Ozcan, Z (Elsevier, 2004)
Objective: To determine the serum lipid profile, the activity of paraoxonase (PON, the lipophilic antioxidant component of HDL-cholesterol), and alterations of the arylesterase activity in preeclamptic women. Study Design: This cross-sectional study included 28 severe preeclamptic, and 24 healthy pregnant women. Fasting venous blood samples were collected during the antepartum period for spectrophotometric determination of the PON and arylesterase activities. Results: In the severe preeclamptic group, the mean levels of total cholesterol, triglycerides, and LDL-cholesterol were 4, 5 and 9.8% higher, respectively, and HDL-cholesterol 9% lower than in the healthy controls. The PON and arylesterase activities were significantly lower in the severe preeclamptic women than in the controls, P < 0.001 and P = 0.000, respectively. A moderately positive correlation was detected between the serum levels of HDL-cholesterol and PON (r = 0.49, P < 0.02, n = 52) and between HDL-cholesterol and arylesterase (r = 0.42, P < 0.05, n = 52). Conclusions: Our results suggest that an abnormal lipid profile and decreased PON and arylesterase activities may have a role in pathogenesis of preeclampsia. (C) 2003 Elsevier Ireland Ltd. All rights reserved.
Keywords: preeclampsia; HDL-cholesterol; LDL-cholesterol; paraoxonase (PON); arylesterase